Recent advances in polymers as additives for wellbore cementing applications: A review; Fuel; Vol. 357. Pt. A - Davoodi Sh. Shadfar; Al-Shargabi M. A. T. S. Mokhammed Abdulsalam Takha Sallam; Wood D. A. David; Rukavishnikov V. S. Valery Sergeevich (2024, 2024)
Title screen